1990
DOI: 10.1161/01.str.21.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory evoked potentials in rat cerebral cortex before and after middle cerebral artery occlusion.

Abstract: We recorded somatosensory evoked potentials in pentobarbital-anesthetized rats before and after middle cerebral artery occlusion. Trigeminal (vibrissae), median (forelimb), and sciatic (bind limb) nerve stimuli produced consistent, robust, and sharply localized responses in the trigeminal, forelimb, and hind limb regions of the somatosensory cortex of 18 rats. These regions are situated at sequentially greater distances from the center of infarcts produced by middle cerebral artery occlusion. In eight rats, oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 24 publications
5
37
0
Order By: Relevance
“…SSEP recording of the primary somatosensory cortex in healthy animals revealed a typical waveform with a first positive peak (P1) followed by a first negative (N1) and a second positive peak, similar to the SSEP signals recorded from intracranially or transcranially implanted electrodes (Sakatani et al, 1990;Ogawa et al, 2000;Gsell et al, 2006). No significant interhemispheric differences for latency of P1 (mean Ϯ SD; P1 left , 12.4 Ϯ 0.6 ms; P1 right , 12.3 Ϯ 0.5 ms; p ϭ 0.62), for N1 latency (N1 left , 18.3 Ϯ 0.8 ms; N1 right , 18.2 Ϯ 1.3 ms; p ϭ 0.71), or for the amplitude between these two peaks (amplitude left , 31 Ϯ 9.3 V; amplitude right , 33.8 Ϯ 9.7 V; p ϭ 0.21) were observed.…”
Section: Electrical Activity and Hemodynamic Response After Strokesupporting
confidence: 56%
“…SSEP recording of the primary somatosensory cortex in healthy animals revealed a typical waveform with a first positive peak (P1) followed by a first negative (N1) and a second positive peak, similar to the SSEP signals recorded from intracranially or transcranially implanted electrodes (Sakatani et al, 1990;Ogawa et al, 2000;Gsell et al, 2006). No significant interhemispheric differences for latency of P1 (mean Ϯ SD; P1 left , 12.4 Ϯ 0.6 ms; P1 right , 12.3 Ϯ 0.5 ms; p ϭ 0.62), for N1 latency (N1 left , 18.3 Ϯ 0.8 ms; N1 right , 18.2 Ϯ 1.3 ms; p ϭ 0.71), or for the amplitude between these two peaks (amplitude left , 31 Ϯ 9.3 V; amplitude right , 33.8 Ϯ 9.7 V; p ϭ 0.21) were observed.…”
Section: Electrical Activity and Hemodynamic Response After Strokesupporting
confidence: 56%
“…However, somatosensory evoked potential (SEP) amplitude increased to 124% and 132%, respectively, during the hyperacute and acute periods. Meyer et al 29 also found an increase in contralateral SEP amplitude during both the hyperacute and acute periods, as did Sakatani et al 30 for contralateral hind limb SEP. Andrews and Muto (unpublished data, 1990), during the hyperacute period in a miniature swine unilateral brain retraction ischemia model, noted an average increase in contralateral auditory evoked potential or SEP amplitude to 121%.…”
Section: Hyperacute and Acute Time Periodsmentioning
confidence: 66%
“…2 ' 24 We recently observed that MCAo transiently abolished evoked potentials in the forelimb and hindlimb somatosensory cortex even though the infarct did not involve these areas. 25 These findings suggest that MCAo causes widespread physiologic disruption of the cortex beyond the infarct site.…”
Section: Discussionmentioning
confidence: 97%